A quantitative framework for evaluating the impact of biodiversity offset policies. (August 2018) - Peterson, I.; Maron, M.; Moillanen, A.; Bekessy, S.; Gordon, A.
Abstract: We propose an impact evaluation framework for biodiversity offsetting that can be used to determine the impacts attributable to developments and their associated offsets under a range of assumptions. This framework is used in conjunction with two hypothetical models of the offsetting process to illustrate a number of issues that can arise when conducting impact evaluations of biodiversity offsetting, where the 'intervention' comprises a development and its associated offsets. We establish that including gains due to avoided losses (i.e. development that would have otherwise happened) in the intervention impact calculation results in a reduction in the offset requirements per unit of development. This occurs regardless of whether the biodiversity at the development or offset sites is declining, stable, or improving. We also show how including gains due to avoided loss requires the consideration of offsets that might otherwise have occurred. These 'avoided offsets' increase the offset requirements per unit of development regardless of the background site dynamics. Finally, we examine offsetting as part of a larger, spatially strategic scheme and show that when the development and offset regions are separated, including avoided loss in the impact calculations can result in a situation where the development impact goes to zero and a system that attains 'net gain' regardless of the development and offsetting activities. The proposed framework can be used to inform offset policy by providing a transparent and logical methodology for the determining the offset requirements for the impacts attributed to development.